Desenvolvimento de bebidas tipo kombucha obtidas a partir de chás das folhas e dos caules da vinagreira (Hibiscus sabdariffa L.) - MENDONÇA, Gislane Romano (2021)
Kombucha is defined as a sweet fermented beverage that has been consumed because of its health benefits. Although black and green teas are the most common substrates for the kombucha production, there are reports that infusions prepared from different plants can be used. Therefore, the aim of this study was to develop kombucha-type beverages from the leaf and stems teas of Hibiscus sabdariffa L. For this, the study was divided into two stages. In the first stage, the extracts from leaf (LV) and stems (SV) flours of vinegar characterization were carried out. In the second stage, they were produced as kombucha-type drinks from these substrates. The beverage production, in turn, was divided into three stages. In the first stage, the conditions for the microorganism’s growth in LV and SV teas. In the second stage, the microorganism’s kinetics of the best formulations were evaluated during 10 days. In the third stage, the beverages were flavored with grape. In addition, the data from the LV and SV beverages were compared with the traditional beverage from green tea. The beverages were divided into 3 treatments: non-fermented, fermented, and fermented and flavored. According to the results obtained, the extracts of LV had higher phenolics and flavonoids content. Moreover, the extracts of LV and SV had antibacterial activity against Staphylococcus aureus resistant to methicillin, Escherichia coli, S. aureus and Candida albicans. For the beverage production, the optimum conditions for the LV production were 5.93% of flour and 5.81% of sucrose. For beverages from SV, it was 4.75% flour and 9.30% sucrose. For the microbial growth, SV presented as the most promising matrix for beverage production. For the data from the third stage, the phenolic compounds and antioxidant activity increased with fermentation and flavoring of the beverages. For the physico-chemical characteristics, the pH values, volatile acidity and alcoholic content were in accordance with the identity and quality standards established in the Brazilian legislation and the alcohol content values characterized the beverages as alcoholic. For the sensory evaluation, the LV and SV drinks had good acceptance. However, the SV beverage had better acceptance than the LV drink. Thus, LV and SV are good substrates for the kombucha-type beverages production, with the stem beverage showing the best acceptance.